GENERATION OF THREE-DIMENSIONAL SPHEROIDS FROM MOUSE MESENCHYMAL STEM CELL - Sekenova, A.Y.; Rakhymzhanova, A.K.; Li, E.A.; Ogay, V.B. (Eurasian Journal of Applied Biotechnology, 2019)
In comparison with two-dimensional (2D) culture, three-dimensional (3D) cultures of mesenchymal stem cells (MSCs) in spheroids (3D spheroids) offer a more physiologically realistic condition. Accordingly, 3D culture has been used to improve the immunomodulatory properties of MSCs and their survival after transplantation. Several methods have been developed to generate 3D spheroids of MSCs to date; however, these methods are time-consuming or expensive, thus limiting their wide application. In this study, we compared two inexpensive and simple culture methods for the generation of 3D spheroids from the MSCs of mouse compact bone: pellet culture and rotating vessels using low-binding 96-well plates. The effectiveness of the two methods was determined by the number of obtained spheroids, their diameter, and the expression of the MSC marker CD44 using morphometric and immunofluorescent methods. A higher number of homogeneous 3D spheroids was obtained from the MSCs of compact bone using a rotating vessel compared to that obtained with pellet culture. The immunofluorescence assay further showed that the developed 3D spheroids highly expressed CD44 on the cell surface. Thus, we suggest that the method of rotating vessels is effective for generating 3D spheroids from the MSCs of compact bone. This method can be used to promote research on the biology of stem cells and develop new therapeutic approaches in cell therapy and regenerative medicine.